Room temperature spectral hole burning observed in Sm-doped mixed crystals - Jin, Z.Z.; Yu, B.Y.; Bae, H.S.; Byun, C.H.; Kim, C.H.; Jang, K.-W.; Lee, J.I. (CLEO/Pacific Rim 1999 - Pacific Rim Conference on Lasers and Electro-Optics, 1999)
For next generation high density optical storage, extensive studies on persistent spectral hole burning (PSHB) have been performed, because they have a large potential for a high density frequency-domain optical data storage. PSHB has been observed at room temperature in Sm-doped crystals and glasses. Among them, glasses are considered to be more favorable than single crystals, due to their wide inhomogeneous line width and easy process for mass production. In the study, we developed a new glass mixture which shows room temperature PSHB with a inhomogeneous line width broadened up to 70 cm-1. The PSHB was characterized by investigating the time decay pattern of fluorescence and the excitation spectra. ？ 1999 IEEE.